Microbiology and management of Staphylococcus aureus lacrimal system infections: A 10-year retrospective study. - Niloufar Bineshfar; Kevin D Clauss; Wendy W Lee; Darlene Miller (PLoS ONE)
Purpose To assess the in vitro efficacy of common antimicrobial agents used empirically for methicillin- resistant and sensitive Staphylococcus aureus (MRSA and MSSA) infections of the lacrimal system. Methods A retrospective review of culture-proven S. aureus isolates retrieved from lacrimal system samples collected between January 2013-December 2022 was performed. Microbiologic characteristics such as in vitro susceptibility as well as clinical characteristics including history of recent ocular surgery, presence of lacrimal biomaterial implant, anti-microbial regimen, and treatments outcome were collected. Results One hundred and sixteen S. aureus isolates (patients = 116) were identified. Thirty-one (27.4%) and 22 (19.5%) patients had recent ocular procedure and lacrimal intubation, respectively. Fifty (44.2%) patients received a combination of oral and topical antibiotics as first line of treatment. The most common empirically utilized antibiotics were β-lactams (38.9%) and polymyxin B/ trimethoprim (31.0%). The antibiotic regimen was changed at least once in 20.5% of patients due to ineffectiveness. Of the patients with positive cultures from the lacrimal excretory apparatus, 37.3% underwent surgery as part of the treatment approach. Of all isolates identified 44.8% were MRSA. Among the fluoroquinolones, the resistance rate was 38.8% for ciprofloxacin and 30.4% for moxifloxacin, with significantly higher resistance rates in MRSA (P-value <0.0001). The resistance rates for trimethoprim/sulfamethoxazole (TMP/SXT) and gentamicin were 8.6% and 3.4%, retrospectively. Conclusions There is low in vitro efficacy of commonly used antimicrobials such as β-lactams and fluoroquinolones in our study population; thus, we recommend opting for trimethoprim/sulfamethoxazole and gentamicin for systemic and topical single-agent treatments.